решите пожалусто 6х+(3х-2)=14 5=-1-(3-9х) 9-(8х-11)=12 (6х+1)-(3-2х)=14 (6-2Х)+4=-5Х-3

0 голосов
33 просмотров

решите пожалусто

6х+(3х-2)=14 5=-1-(3-9х) 9-(8х-11)=12 (6х+1)-(3-2х)=14 (6-2Х)+4=-5Х-3


Алгебра (16 баллов) | 33 просмотров
Дано ответов: 2
0 голосов

6x+(3x-2)=14   6x+3x-2=14   9x=14+2   9x=16     x=16/9

5=-1-(3-9x)   5=-1-3+9x   5+4=9x   9x=9   x=1

9-(8x-11)=12   9-8x+12=12   -8x=-9    x=9/8

(6x+1)-(3-2x)=14    6x+1-3+2x=14    8x-2=14    8x=16   x=2

(6-2х)+4=-5x-3    6-2x+4=-5x-3     5x-2x=-3-10    3x=-13      x=-13/3

(107 баллов)
0 голосов

х+3х-2=14

4х=14+2

4х=16

х=16:4

х=4

(100 баллов)